2020
DOI: 10.3390/microorganisms8101524
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Effects of Curcumin on Adenovirus Replication

Abstract: Human adenovirus (HAdV) is a common pathogen that can cause severe morbidity and mortality in certain populations, including pediatric, geriatric, and immunocompromised patients. Unfortunately, there are no approved therapeutics to combat HAdV infections. Curcumin, the primary curcuminoid compound found in turmeric spice, has shown broad activity as an antimicrobial agent, limiting the replication of many different bacteria and viruses. In this study, we evaluated curcumin as an anti-HAdV agent. Treatment of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Treatment with curcumin also decreased HAdV-5 viral genome copy numbers, as well as reduced virus recovery as determined by plaque assay [81]. However, the most effective concentrations of curcumin were only slightly lower than the CC 50 (~68 µM) of curcumin in this cell line, indicating that curcumin may have only a very narrow therapeutic window against HAdV [81].…”
Section: Human Adenovirusmentioning
confidence: 87%
See 2 more Smart Citations
“…Treatment with curcumin also decreased HAdV-5 viral genome copy numbers, as well as reduced virus recovery as determined by plaque assay [81]. However, the most effective concentrations of curcumin were only slightly lower than the CC 50 (~68 µM) of curcumin in this cell line, indicating that curcumin may have only a very narrow therapeutic window against HAdV [81].…”
Section: Human Adenovirusmentioning
confidence: 87%
“…Our group evaluated curcumin against human adenovirus (HAdV). In A549 human lung adenocarcinoma cells infected with HAdV types 4, 5 or 7, curcumin (0-100 µM) caused a dose-dependent decrease in expression of the viral early 1A (E1A) proteins, which are vital for the virus to complete its replicative cycle [80,81], indicating curcumin is effective against multiple types of HAdV. Treatment with curcumin also decreased HAdV-5 viral genome copy numbers, as well as reduced virus recovery as determined by plaque assay [81].…”
Section: Human Adenovirusmentioning
confidence: 99%
See 1 more Smart Citation
“…The A549 human lung adenocarcinoma cells were infected with human adenovirus types 4, 5, and 7 and the effect of curcumin showed that curcumin reduced the expression of viral early protein 1 (E1A) in several types of this virus. Curcumin also reduced the genome copy number of virus that were determined with plaque assay [74,75].…”
Section: Adenovirusmentioning
confidence: 99%
“…Treatment of the infected cells with 50 µM of curcumin for a period of 8hrs of infection showed that it prevented the expression of the E1A and when treated with curcumin for 1hr of infection, did not reduce the E1A protein showing that curcumin does not inactivate the virus or prevent the internalization. 41…”
Section: Human Adeno Virusmentioning
confidence: 99%